Dari Mahanian ke Corbettian: Proyeksi Strategi Angkatan Laut Kontemporer India dalam Menanggapi Kehadiran Tiongkok di Kawasan Samudra Hindia - Pramudia, Putu Shangrina (HUMANIORUM, 2025)
This paper examines the shift in India's naval strategy from Mahanian to Corbettian principles in response to China’s growing maritime presence in the Indian Ocean Region (IOR). While India historically followed Mahan’s focus on decisive battles and maritime dominance, the increasing assertiveness of China’s People’s Liberation Army Navy (PLAN) necessitated a strategic pivot. Adopting Corbett’s emphasis on political objectives, the Indian Navy now prioritizes sea control, sea denial, the protection of Sea Lines of Communication (SLOCs), and maritime diplomacy. This transition reflects India’s need for a more pragmatic, politically driven approach to safeguard its strategic interests in the face of China's maritime ambitions.